Levels and Predictors of Knowledge, Attitude, and Practice Regarding the Health Hazards Associated With Barber's Profession in Fiji - Dip Chand MSc; Masoud Mohammadnezhad PhD; Sabiha Khan MSc (SAGE Publishing, 2022)
Introduction: This study aimed to determine the level and predictors of Knowledge, Attitude and Practice (KAP) among barbers regarding health hazards associated with their profession in Fiji. Methods: A quantitative study was used to assess the levels and predictors of KAP using a structured questionnaire among 117 barbers who were chosen between June and November 2020 in Suva, Fiji. All those barbershops that operated at least for 6 months, were licensed, and 18 years and above were included. A self-administrative closed-ended structured questionnaire was used to collect data. The level of KAP was assessed using the modified Bloom's cut-off points. A correlation test was used to determine predictors of KAP. Results: The majority of participants had a medium level of knowledge (62.4%), medium level of attitude (63.2%), and low level of practice (64.1%) towards health hazards associated with barbering the profession. However, 28.2% had low knowledge and attitude scores. The major source of knowledge was through the internet. The results of the correlation test showed that religion, education level, and weekly income were significantly correlated with knowledge (<.05) whereas age and weekly income was significantly correlated with the level of attitude of participants towards health hazards associated with their profession (<.05). Conclusion: Barbers had medium knowledge and attitude towards health hazards associated with the barbering profession while their practice was poor. These findings call for prompt and target group interventions such as strengthening enforcement, awareness, training on equipment decontamination and Good Hygiene Practices to be conducted.